eCREST: a novel online patient simulation resource to aid better diagnosis through developing clinical reasoning - Kassianos, Angelos P.; Plackett, Ruth; Schartau, Patricia; Valerio, Christopher; Hopwood, Jenny; Kay, Natasha; Mylan, Sophie; Sheringham, Jessica (My University, 2020)
In this In Practice report, we describe a novel educational resource using online patient simulations- the electronic Clinical Reasoning Educational Simulation Tool (eCREST). eCREST seeks to improve the quality of diagnoses from common respiratory symptoms seen in primary care by focusing on developing clinical reasoning skills. It has recently been tested with final-year medical students in three UK medical schools. In response to interest, we are exploring the use of eCREST to other medical schools in the UK and internationally and to other professional groups and will conduct further evaluation.
Keywords: patient simulations; clinical decision making; education; diagnosis